Critical success factors for social CRM strategies for South African companies - Reynecke, Taryn (My University, 2015)
Social CRM is a new buzz word in the marketing and technology fields and has become an important strategic initiative for companies to employ. Social CRM arose from the need to transform the way we communicate with our customers due to the emergence of social media. In South Africa Social CRM is still a relatively new field with not many companies implementing it successfully. This research explores the benefits of implementing a Social CRM strategy as well as what the critical success factors are for implementing such a strategy. Five organisations that are implementing Social CRM were identified and eleven managers within those companies were interviewed. Eight companies that provide CRM or social media services for their clients were also identified and one executive or manager was interviewed from each. The respondents were interviewed over email using a semi-structured interview approach, which yielded qualitative data. The data was analysed using content analysis, more specifically, thematic content analysis and concept mapping to determine recurring themes. Findings from the interviews resulted in nine benefits of implementing Social CRM and seven critical success factors of Social CRM. The findings of this research shows that the benefits gained from implementing Social CRM are great and include reduced costs, improved customer service, increased reputation and brand building, better segmentation and targeting of customers, enhanced communication and customer collaboration, interactive customer engagement, improved customer insight, increased sales and proactive issue resolution. It also shows that companies need to ensure certain factors are successfully put in place when implementing Social CRM strategies. The critical success factors include organisational readiness (strategy, culture and processes), commitment and buy-in (champion leadership, company-wide commitment and buy-in, senior management commitment and buy-in, staff commitment and buy-in), interaction with customers, knowledge and skills, technology, relevant, high quality content and measurement and monitoring.
Thesis (M.M. (Strategic Marketing))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.